2019
DOI: 10.3126/nccj.v4i1.24746
|View full text |Cite
|
Sign up to set email alerts
|

Herding Behavior in Nepali Stock Market: Empirical Evidences based on Investors from NEPSE

Abstract: The research paper aims to examine the attitudinal factors influencing herding behavior in order to manage the fluctuations, bubbles, and bursts in the Nepal capital market. The descriptive and analytical research design has been adopted in the study. The qualitative data has been collected through the structured, self-administered questionnaire distributed to five hundred investors of the securities market in Nepal. The usable questionnaires have been confined to 407responses. The statistical tools mean, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
1
Order By: Relevance
“…These findings are in line with the assertions of Komalasari et al (2021), who in their study conducted an extensive review of the literature regarding herding and found socio-economic factors as least influential towards herding. Contrary, these results contradict several previous studies that posited socioeconomic factors as the significant driver of herd behavior (Nair and Yermal, 2017; Wong, 2018; Risal and Khatiwada, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with the assertions of Komalasari et al (2021), who in their study conducted an extensive review of the literature regarding herding and found socio-economic factors as least influential towards herding. Contrary, these results contradict several previous studies that posited socioeconomic factors as the significant driver of herd behavior (Nair and Yermal, 2017; Wong, 2018; Risal and Khatiwada, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Individual investors are also influenced by a sociological force (Nair and Yermal, 2017; Wong, 2018; Risal and Khatiwada, 2019). Social influence plays a critical role in formulating an individual persons' insight about others, with respect to the target behavior and whether they expect one individual to perform that behavior or not (Ajzen, 1991).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The paper found that political instability is the major challenge and the overloaded information, which is difficult to filter, made decision-making harder for Nepalese investors, which was contradictory to Risal and Khatiwada (2019). They found that the hasty decisions making process and the herd behaviour among the Nepalese investors made them go for wrong investment decisions.…”
Section: Theme 5: Investor's Investment Decisions Go Wrongmentioning
confidence: 99%
“…To make such accurate decisions, investors are faced with different challenges. Risal and Khatiwada (2019) found that Nepalese investors were doing hasty decisions with herd behaviour while investing in NEPSE. Hence, the following opinions forwarded by interviewees reflect the challenges in making investment decisions at NEPSE: Frankly speaking, the unnecessary flow of information (cannot say relevant or irrelevant) especially on social media, makes investment decisions more complex.…”
Section: Theme 3: Investor's Priorities In Company Selection For Investingmentioning
confidence: 99%
“…Risal (2016) had also explained the scenario and the importance of capital market development in Nepal. In addition, Risal and Khatiwada (2019) had explained the herding behavior in Nepalese capital market. The result had revealed the significant relationship of hasty decision with herd behavior.…”
Section: Thematic Analysismentioning
confidence: 99%